A semantic framework for the abstract model checking of tccp programs - Alpuente, María; del Mar Gallardo, María; Pimentel, Ernesto; Villanueva, Alicia (Theoretical computer science, 2005)
The Timed Concurrent Constraint programming language ( tccp) introduces time aspects into the Concurrent Constraint paradigm. This makes tccp especially appropriate for analyzing timing properties of concurrent systems by model checking. However, even if very compact state representations are obtained thanks to the use of constraints in tccp, large state spaces can still be generated, which may prevent model-checking tools from verifying tccp programs completely. Model checking tccp programs is a difficult task due to the subtleties of the underlying operational semantics, which combines constraints, concurrency, non-determinism and time. Currently, there is no practical model-checking tool that is applicable to tccp. In this work, we introduce an abstract methodology which is based on over- and under-approximating tccp models and which mitigates the state explosion problem that is common to traditional model-checking algorithms. We ascertain the conditions for the correctness of the abstract technique and show that this preliminary abstract semantics does not correctly simulate the suspension behavior, which is a key feature of tccp. Then, we present a refined abstract semantics which correctly models suspension. Finally, we complete our methodology by approximating the temporal properties that must be verified.